The Role and Challenges of Grammar Teaching in Developing Students' English Writing Skills - Armadi, Samsu (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
Grammar teaching plays a crucial role in developing students' English writing skills, particularly at the university level. Academic writing demands the use of appropriate grammatical structures to convey ideas logically and clearly. However, in practice, grammar teaching faces various challenges, such as lack of student interest, monotonous learning methods, and limited learning time. This study aims to examine the role of grammar teaching and the challenges faced in improving students' writing skills. This study used a descriptive qualitative approach, using observation, interviews, and document analysis as data collection techniques. This study demonstrates that a good understanding of grammar significantly contributes to the quality of students' writing. However, challenges such as negative transfer from the first language (L1), low learning motivation, and a lack of varied pedagogical approaches require attention. These findings suggest the need for innovation in grammar teaching methods to effectively support the improvement of students' writing skills.